A Sustainable Household IoT E-waste Management Guideline in Malaysia - MOHAMAD RAZIP, MARYM (2021)
The Internet of Things (IoT) plays a huge part in the current Fourth Industrial Revolution which turned out to be one of the fastest contributors towards technological development around the world including Malaysia